Scholarly Publication and Collaboration in Brazil: The Role of Geography - Otavio Sidone; Eduardo Haddad; Jesus Mena-Chalco (European Regional Science Association (ERSA), 2014)
Brazilian scholarly outputs have had rapid growth that was accompanied by an expansion of domestic research collaboration. In this paper, we identify spatial patterns of research collaboration in Brazil, as well as measure the role of geographical proximity in determining the interaction among Brazilian researchers. Using a database comprised of over one million researchers and seven million publications registered in the Brazilian Lattes Platform, we collect and consolidate information on inter-regional research collaboration in terms of scientific co-authorship networks among 4,616 municipalities over the period between 1992 and 2009, which enabled a range of data analysis unprecedented in literature. The effects of geographical distance on collaboration are measured for different knowledge areas under the estimation of spatial interaction models. The main results suggest strong evidence of geographical deconcentration of collaboration in recent years with an increased participation of authors in scientifically less traditional regions, such as South and Northeast Brazil. Additionally, the distance still is significant in determining the intensity of knowledge flows in scientific collaboration networks in Brazil since the increase of 100 kilometers between two researchers implies the average reduction on 16% of the probability of collaboration and there is no evidence that its effect has diminished over time, although the magnitude of such effects varies among networks of different knowledge areas.
Keywords: R12; 330; spatial scientometrics; scientific collaboration; co-authorship networks; spatial interaction models